2015
DOI: 10.1590/1516-1439.022115
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of a Translucent Fiberglass Post on the Polymerization of Dual Cure Resin Cement Analyzed by Electron Paramagnetic Resonance

Abstract: Electron Paramagnetic Resonance (EPR) was used as an alternative method to study the conversion degree of dual cure resin cement and verify the influence of prefabricated translucent fiberglass post on the dual cure resin cement polymerization at different restoration points. The post cementation of White Post DC (FGM, Joinville, SC, Brasil) was simulated using the dual cured resin cement Allcem (FGM, Joinville, SC, Brasil) in three different protocols: cement irradiated for 40 s; no light irradiation and ceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…Proportionality was observed between the FR concentration and quality of the resinous material, indicating that EPR spectroscopy is an important tool for understanding these dental restorative materials [22]. These data are in accordance with Salomão et al [24]. In that case, authors studied the influence of the irradiation protocol in the depth of cure and observed that the irradiation protocol influences only in the first 8 mm of the 20-mm long double-shaped translucent fiberglass post.…”
Section: Resultssupporting
confidence: 84%
“…Proportionality was observed between the FR concentration and quality of the resinous material, indicating that EPR spectroscopy is an important tool for understanding these dental restorative materials [22]. These data are in accordance with Salomão et al [24]. In that case, authors studied the influence of the irradiation protocol in the depth of cure and observed that the irradiation protocol influences only in the first 8 mm of the 20-mm long double-shaped translucent fiberglass post.…”
Section: Resultssupporting
confidence: 84%
“…First, we focused on Mn­(acac) 3 /Dket1 interaction. Interestingly, in Figure A, the final polymer cured using Mn­(acac) 3 /Dket1 (curve 1) or BPO/4- N , N -TMA (curve 2) shows radicals trapped in the polymer matrix at 3500 ± 50 G (see also Figure B), in line with the literature. On the contrary, the signal of the polymer is clearly showing six bands typical of Mn­(II) when the Mn­(acac) 3 /Dket1 initiating system is used (Figure A, curve 1); we can therefore clearly expect that some Mn­(II) are trapped in the polymer after reaction. In other words, it strongly suggests the reduction of Mn­(III) to Mn­(II) by Dket1.…”
Section: Resultssupporting
confidence: 83%
“…Nevertheless, KF posts are less translucent than everStick ® and other commercial glass fiber posts. It has been suggested that the ability of light to be transmitted along translucent posts could increase the conversion degree of light-cured resin cements with a consequent improvement of their mechanical properties, however, the efficiency of this propagation, especially in the deeper regions has still to be investigated 33) . A previous report showed no significant difference in root dentine bond strength values between translucent and opaque fiber posts 34) .…”
Section: Discussionmentioning
confidence: 99%